A Quality Assessment of Commonly Vended Tomato, Plum and Mint Sauces in Kamoke, Pakistan - Javed, Anam; Nazeer, Aqsa; Ghulam Hyder, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Sauces are food additives that are frequently consumed globally and especially with fast food in Pakistan but often their consumer quality related issues are noticed. That is why; current study was designed to examin selective physicochemical properties and microbial contamination in commonly vended tomato, plum and mint sauces in Tehsil Kamoke, District Gujranwala, Punjab, Pakistan. In this experimentation, total 15 samples were collected (5 samples of each plum, mint and tomato sauces) from a uniform distance of 2 km accorAding to the map of Kamoke. For microbial culture based analysis, selective tests were done to mainly detect coliforms and results were statistically evaluated by applying one way ANOVA. The physicochemical parameters like pH and sugar content were found significant at 0.01% level for sauces of mint (4.32) and for plum (15.54%), respectively. Among artificial sweeteners aspartame was totally absent in all samples but saccharine was present in some samples in greater amount than standard consumption values. The mint sauce samples were found contaminated (488CFU/ml) at 5% significance level. Similarly, for coliforms (472 to 568.6 CFU/ml) of selected locally vended plum, mint and tomato sauces were noted. Microbial contaminants included Staphylococcus epidermis, Bacillus simplex, Escherichia coli, Salmonella spp, Arthrobacter dextranolyticus, Pseudomonas cidrella, Bacillus weihenstephanesis, Enterobacter aerogenus, Klebsiella pneumonia, Pseudomonas aeroginosa and Proteus mirabilis. During sampling, it was observed that mostly sauces were exposed to high temperature and were placed uncovered. Vendors were unaware of personal hygiene, proper handling, storage and quality control standards for sauces which results in adulteration and contamination. It is recommended that to improve the quality of commonly vended sauces, their regular inspection along with the programmed general public awareness should be organized.